2017
DOI: 10.1051/matecconf/201711101001
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction by natural polymeric additives in PMDS microchannel: Effect of types of additives

Abstract: Abstract. 'UDJ UHGXFWLRQ WHFKQRORJ\ ZDV XVHG LQ PHGLFDO DSSOLFDWLRQV WR HQKDQFH WKH EORRG IORZ LQ VHPL FORJJHG EORRG VWUHDPV ZKLFK FDQ EH DQ DOWHUQDWLYH WUHDWPHQW IRU DWKHURVFOHURVLV ,Q WKLV SUHVHQW VWXG\ QDWXUDO SRO\PHULF GUDJ UHGXFLQJ DGGLWLYHV '5$ ZDV LQWURGXFHG WR UHSODFH V\QWKHWLF SRO\PHU ZKLFK KDV WKH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
2
2
Order By: Relevance
“…8. 8 d and 8 e. The results were contradictory to literature [35] where one of the tested additives would maintain its high flow enhancement performance regardless of the other operating conditions. It can be clearly seen that different types of additives showed its maximum %FI under different conditions like concentrations and operating pressure.…”
Section: Effect Of Type Of Additivescontrasting
confidence: 66%
See 2 more Smart Citations
“…8. 8 d and 8 e. The results were contradictory to literature [35] where one of the tested additives would maintain its high flow enhancement performance regardless of the other operating conditions. It can be clearly seen that different types of additives showed its maximum %FI under different conditions like concentrations and operating pressure.…”
Section: Effect Of Type Of Additivescontrasting
confidence: 66%
“…Higher concentrations of okra (700 and 1000 ppm) performed as better DRAs compared to the other two mucilages under the same condition as demonstrated in Figs. 8 d and 8 e. The results were contradictory to literature [35] where one of the tested additives would maintain its high flow enhancement performance regardless of the other operating conditions. This phenomenon indicated that the flow enhancement operation is the complex interaction from different aspects including the properties of additives (density, molecular weight, and structure), concentration of the solution added, flow conditions, and even the design of the test section, in this case the design of the microchannel.…”
Section: Effect Of Type Of Additivescontrasting
confidence: 66%
See 1 more Smart Citation
“…A few attempts were made by Abdulbari et al [27,28] to utilize these additives as effective drag reducing agents in pipelines. Several types of additives from different plants were successfully investigated as DRA such as aloe vera [29], hibiscus leaves [30,31], and okra [27,28]. Despite the excellent drag reduction performance of the proposed organic polymers, all these additives showed low stability against shear forces exerted by pumps, valves and joints.…”
Section: Introductionmentioning
confidence: 99%